Decision support for evaluating player performance in rugby union - Calder, J. M.; Durbach, I. N. (International Journal of Sports Science and Coaching, 2015)
Many professional rugby teams collect extensive data on player performance, but the synthesis of this data into overall evaluations and subsequent selections is still largely left to the expert but unassisted judgment of coaching staff. Decision support systems are designed to assist this process by providing a framework for making decisions in a structured, transparent way. In this article we develop a decision support tool to assist performance evaluation in rugby. The method considers player performance over a range of attributes and addresses uncertainty both in the assessment of performance and in preferences for certain aspects of the game over others. We illustrate the approach using data collected for the 2008 and 2009 Super Rugby tournament.